Etiologies and Microbiological Profile of Complicated Urinary Tract Infections, among Patients Admitted in a Tertiary Care Hospital - Syed, Beenish; Salahuddin, Naseem; Ishtiaq, Hira (Infectious Diseases Journal of Pakistan, 2023)
Background: Urinary tract infections (UTIs) are one of the most prevalent infections worldwide, with an estimated incidence of 18/1000 person per year. A complicated urinary tract infection(cUTI) is defined as an infection of the upper or lower urinary tract, with either a structural or functional abnormality. Such infections present a challenge for clinicians because of greater frequency of resistant microorganisms, prolonged treatment and recurrences. Objective: To describe the etiologies, demographic characteristics and microbiological profile of patients admitted with Complicated Urinary tract infections in a tertiary care hospital. Methods: This is a retrospective analysis through medical chart review of all patients admitted to the hospital, who met the criteria of complicated UTI, from January 2008 to March 2016. Data was extracted concerning demographics, etiologies, severe clinical manifestations, micro organisms implicated and frequency of multidrug resistant organisms. Data was entered into SPSS version 21, analyzed and expressed as median, range, numbers or percentage. Results: 206 patients were included in the study, 101 (49%) were males. Median (IQR) age was 45 (16-62) years. Commonest etiologies identified were obstruction in 81 (39%), prior use of antibiotics 81 (39%), diabetes mellitus 71 (34%), chronic renal insufficiency 71 (34%) and indwelling catheter in 68 (33%). The most common organism seen in both blood and urine cultures were Escherichia Coli, with Multi drug resistant organisms in 87% in blood, and 69% in urine. Sepsis was present in 82% and renal failure in 58% patients. Conclusion: Given the varied etiologies, high prevalence of resistant microorganisms and severe manifestations, identification of underlying conditions and appropriate use of antimicrobials is imperative in decreasing the severity of cUTI. Key words: cUTI, Multidrug resistance